Structures Congress 2015 2015
DOI: 10.1061/9780784479117.097
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Resistance to Progressive Collapse of Steel and Composite Moment Frames

Abstract: It has sometimes been presumed that the ability of buildings designed to resist seismic loading will inherently be superior to that of those designed for nonseismic conditions. This assertion is tested herein by comparing the resistance to progressive collapse of a series of representative moment frames. The assessments are undertaken using the alternate load path approach to sudden column loss, implemented by means of a technique developed at Imperial College London. The findings confirm that the greater mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In this case, the total width is 28 m in the x and y directions (Figure 2). The use of low and medium-rise buildings is designed to be used in examining the change of system properties, as in many other studies in the literature (Denavit et al 2014b(Denavit et al , 2016aEtli 2021b;Güneyisi 2020c, 2021b;Hajjar 2002;Judd and Pakwan 2018a;Nethercot and Vidalis 2015;Silva et al 2016a;Skalomenos, Hatzigeorgiou, and Beskos 2015a). Considering the region covered in this study, the regional worst possible earthquake scenario problem is discussed.…”
Section: Example Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the total width is 28 m in the x and y directions (Figure 2). The use of low and medium-rise buildings is designed to be used in examining the change of system properties, as in many other studies in the literature (Denavit et al 2014b(Denavit et al , 2016aEtli 2021b;Güneyisi 2020c, 2021b;Hajjar 2002;Judd and Pakwan 2018a;Nethercot and Vidalis 2015;Silva et al 2016a;Skalomenos, Hatzigeorgiou, and Beskos 2015a). Considering the region covered in this study, the regional worst possible earthquake scenario problem is discussed.…”
Section: Example Structuresmentioning
confidence: 99%
“…Many studies show that severe earthquakes are the main design factor on the structural safety of composite momentresisting frames (CMRF) (Denavit et al 2014b;Hajjar 2002;Lu et al 2019;Nethercot and Vidalis 2015). One of the studies using inelastic analysis of CMRFs dates back about 30 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the SPCRCF, SPCRCF-2 is improved in the following aspects: (1) A 15-mm gap is reserved between the beam and column. (2) The bolt holes in the angle steel and rib stiffeners are made elliptical shape. The purpose of this design is to release the axial force in the beams by allowing moderate slipping between the frame beam and the SAS during the CAA stage.…”
Section: Concept Of Spcrcf-2mentioning
confidence: 99%
“…Indeed, the National Science Foundation (NSF) of the United States indicated that the resistance and sustainable development of structures under multi-hazard and complex environments should be improved [1]. Previous studies reveal that earthquake actions and progressive collapse events are the primary hazardous causes that impact the structural safety of a conventional steel-concrete composite frame (CSCCF) [2][3][4][5][6][7][8][9]. Thus, many researches have been performed on related critical issues, including the buckling phenomena on both local and system levels [10][11][12][13][14][15], and innovative systems that exhibit self-centering characteristics with replaceable energy-dissipating components [16,17], etc.…”
Section: Introductionmentioning
confidence: 99%